Hukum Perjanjian Pranikah dalam Pandangan Hukum Perdata - Gresnia, Enggel (Universitas Islam Indragiri, 2024)
Humans created by Allah SWT on this earth are basically social creatures and every human being lives side by side with one another. In writing this scientific paper, the author uses library research methods and also uses normative juridical research methods that examine various theories, concepts and legal principles and laws related to this research, where the legal material is Law Number 1 of 1974 concerning marriage. The problems in this paper are (1) What is meant by marriage, (2) What is meant by a prenuptial agreement, (3) The legal provisions of a prenuptial agreement in the view of civil law, (4) whether a prenuptial agreement can be canceled and how to cancel a prenuptial agreement according to civil law, and the conclusions are (1) marriage is one of the phases in human life that can be lived by a Muslim after determining a life partner and being mentally and financially ready and if he is capable and mature and emotionally ready then marriage can be done in order to perfect half of his religion, (2) a prenuptial agreement is an agreement made before or during marriage, and the contents of this prenuptial agreement are to discuss (a) the rights and obligations of husband and wife while being husband and wife, (b) an agreement made without coercion from any party, (c) the contents of this agreement in the form of property and debt, (d) discussing children and offspring if the husband and wife divorce. (3) according to the view of civil law, this prenuptial agreement must fulfill the conditions stated in article 139 of the Civil Code, and in the view of civil law itself an agreement can be made and may be made if it meets the conditions, does not violate decency and the law and uses a notarial deed, (4) according to civil law this prenuptial agreement can be canceled if both spouses agree to change and the change does not harm the third party, namely the notary, and the cancellation of the prenuptial agreement can be done if there is a violation of the agreement and how to cancel this prenuptial agreement can be done through the court, the plaintiff can report the defendant to the religious court if a Muslim and to the district court if non-Muslim